Current concepts of chronic gastritis and gastropathies: new international consensus RE.GA.IN - S.M. Tkach; N.V. Kharchenko; A.E. Dorofieiev; Yu.Z. Hurkalo; L.M. Ryzhiy (Gastroenterologìa)
Recent decades have been marked by several important milestones in the field of gastritis. New epidemiological reports were received, especially from countries with a high incidence of gastric cancer, and H.pylori infection was recognized as the most important cause of gastritis, due to which it was quickly included in the primary infectious oncogenic agents. Clinical strategies for the detection and eradication of H.pylori infection were developed, the previously unsuspected clinical and pathological significance of gastric microbiota was established, and extraordinary progress was made in the technology of esophagogastroduodenoscopy. Histological determination of gastritis in terms of stage (that is, risk stratification of stomach cancer) was implemented into clinical practice. In addition to the Sydney and Houston gastritis classifications, the six editions of the Maastricht Consensus (1996–2022) and the Kyoto Global Consensus deserve special attention, thanks to which broad agreements and significant scientific achievements became possible in the most controversial issues of the entire spectrum of gastritis, with a special emphasis on H.pylori gastritis, which accounts for more than 90 % of all forms of gastritis worldwide. The Real-world Gastritis Initiative (RE.GA.IN) marks the next step in the ongoing search to achieve a better understanding of various gastric conditions. The RE.GA.IN consensus was concluded in Venice in November 2022 after 8 months of intensive global scientific reasonings. RE.GA.IN mission itself has been focused on critically reviewing, updating, sharing and building consensus on the current scientific knowledge of inflammatory gastric lesions. It includes eight sections on clinicopathological topics, each consisting of preamble, which presents brief statements and corresponding explanatory texts. For each statement, the level of evidence (assessed according to a predefined four-level scale) and the strength of recommendations on the GRADE system are reported. The following topics were considered in the consensus: 1) definition and classification issues of gastritis; 2) spectrum of H.pylori gastritis; 3) key diagnosis of H.pylori gastritis; 4) H.pylori gastritis: clinical results; 5) autoimmune gastritis; 6) gastritis of low prevalence; 7) gastritis and gastric microbiota; 8) epidemiology of gastritis and associated precancerous and neoplastic lesions. Thus, the most controversial aspects of gastritis were addressed, a comprehensive and diverse body of knowledge was brought together to use patient-oriented evidence to assist physicians in their real-world clinical practice.